Stapled trans-anal rectal resection for the surgical management of obstructed defecation syndrome: our experience in Bangladesh - Haque, Asif Almas; Talukder, Md Rajibul Haque; Alam, Hasina (BIRDEM Medical Journal, 2020)
Background: Obstructed defecation syndrome (ODS) is one of the commonest constipation related disorders confronted by surgeons in Bangladesh. Stapled transanal rectal resection (STARR) is a novel surgical technique specific for ODS. This study was designed to evaluate the effectiveness of STARR on patients with ODS in Bangladesh. Methods: Thirty (30) female patients (age: 46±13.2 years) with ODS, were selected for this observational study, from July 2016 to July 2019, in a private hospital of Dhaka. Patients were interviewed with standardized questionnaire at study enrolment and up to 3 months postoperatively. Surgical outcome was quantified according to the Longo’s Modified ODS score (MODS). Results: At initial consultation, the mean Longo’s MODS score was 17.6+1.9. Mean operative time was 39+6.2 minutes. Commonest complication was ‘staple line bleeding’ in 24(80%) patients intraoperatively & ‘defecatory urgency’ in 18(60 %) patients postoperatively. At postoperative 3-month follow-up, statistically significant (p<0.05) symptomatic improvement in Longo’s MODS score (6.9+2.5) was observed in 27(90%) patients. Ten (33.3%) of patients judged their final clinical outcome as ‘excellent’, 11(36.7%) as ‘good’, and 6(20%) as ‘moderate’, with 3(10%) having ‘poor/no improvement’. Conclusion: After analyzing our results, we conclude that STARR is an effective procedure for the treatment of ODS due to structural abnormalities and can be performed safely without any major morbidity. Birdem Med J 2021; 11(1): 11-16